1990
DOI: 10.1159/000186179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypocitraturia and Hypopyrophosphaturia in Recurrent Calcium Stone Formers: As Isolated Defects or Associated with Other Metabolic Abnormalities

Abstract: Several underlying metabolic abnormalities may be present in patients with recurrent calcium calculus disease (RCCD). The aim of this study was to determine the prevalence of deficiencies of 2 well-known potent inhibitors of crystal formation and growth, citrate and pyrophosphate, in the various metabolic subgroups and as single defects. In 107 patients with RCCD, urinary citrate was significantly decreased in all metabolic subgroups with 49% of patients having hypocitraturia (2.53 ± 1.19 mmol/24 h) versus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Hypocitraturia is a well-recognized inhibitor defect and has been mainly investigated in adult patients with IH, hyperoxaluria or hyperuricosuria [11,20,21], Our data demonstrated that both SF and NSF had a significant lower citrate/calcium ratio than controls (p < 0.001); in addition, it was also lower in SF than in NSF (p < 0.05; table 4). Other investigators reported a significantly low citrate/Ca ratio in SF, especially in recur rent SF [22,23], Our study showed no difference in citrate excretion between patients and controls.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Hypocitraturia is a well-recognized inhibitor defect and has been mainly investigated in adult patients with IH, hyperoxaluria or hyperuricosuria [11,20,21], Our data demonstrated that both SF and NSF had a significant lower citrate/calcium ratio than controls (p < 0.001); in addition, it was also lower in SF than in NSF (p < 0.05; table 4). Other investigators reported a significantly low citrate/Ca ratio in SF, especially in recur rent SF [22,23], Our study showed no difference in citrate excretion between patients and controls.…”
mentioning
confidence: 51%
“…Some other substances (e.g. magnesium, citrate, glycosaminoglycans, pyrophosphate, zinc) can modify the ability of inorganic microcrystals to grow and form stones [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together with the demonstration of renal epithelial cell expression of ANK and PP export to apical/basal bathing media in vitro, we postulate that pyrophosphate transport to either interstitium or tubular lumen comprises an important mechanism that protects against nephrocalcinosis/nephrolithiasis. Indeed hypopyrophosphaturia has been documented in a group of recurrent stone-forming patients [20]. Ho et al mention that ank-/-animals show renal calcification [9].…”
Section: Discussionmentioning
confidence: 99%
“…If it is equally efficient in urine it can contribute 50% crystal COM growth inhibition in the collecting ducts (5 times dilution) and up to 80% in the urine. Hypopyrophosphaturia is postulated to be a metabolic risk factor for recurrent kidney stone formers [90]. Mutations in pyrophosphate transporter, ANKH , are associated with defects of calcification such as craniometaphyseal dysplasia and chodrocalcinosis.…”
Section: Supersaturation and Crystallization Of Calcium Oxalatementioning
confidence: 99%